2021
DOI: 10.1111/jcap.12359
|View full text |Cite
|
Sign up to set email alerts
|

Mental health risk among children during COVID‐19 lockdown

Abstract: The COVID‐19 pandemic has created a hugely detrimental impact on the psychological health of people around the world. Children are extremely vulnerable; therefore, it is of utmost importance to discuss the prevalence of the symptoms, their associated risk factors, and the strategies to identify and understand their deteriorating mental health (MH) before it leads to disastrous outcomes. Hence, parents and schools should come together in devising modes to create an environment in which children can easily tackl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…Although the negative impact of the lifestyle changes, stay-at-home orders, lockdowns, and therefore social restrictions, was documented for various groups of the population, the adolescents might be especially vulnerable because of the developmental tasks and challenges [ 1 , 2 , 3 , 4 ]. Moreover, school-aged children might be experiencing additional specific strains because of prolonged school closure and distance education, and therefore reduced professional support, reduced social activities, and increased physical isolation from peers [ 3 , 5 , 6 , 7 , 8 , 9 ]. Thus, in adolescence, the additional pandemic challenges might have complicated every aspect of developmental strains and challenges posed by rapid physical and emotional growth itself, including increasing academic demands and expectations, changing social relationships with family and peers, and increasing exposure to online interactions [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the negative impact of the lifestyle changes, stay-at-home orders, lockdowns, and therefore social restrictions, was documented for various groups of the population, the adolescents might be especially vulnerable because of the developmental tasks and challenges [ 1 , 2 , 3 , 4 ]. Moreover, school-aged children might be experiencing additional specific strains because of prolonged school closure and distance education, and therefore reduced professional support, reduced social activities, and increased physical isolation from peers [ 3 , 5 , 6 , 7 , 8 , 9 ]. Thus, in adolescence, the additional pandemic challenges might have complicated every aspect of developmental strains and challenges posed by rapid physical and emotional growth itself, including increasing academic demands and expectations, changing social relationships with family and peers, and increasing exposure to online interactions [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The female gender was found to be associated not only with mental health problems, but also more time spent sedentarily and less physical activity [ 2 , 11 , 17 , 19 , 26 , 31 , 32 ]. Preexisting health problems [ 1 ] and vulnerability due to previous and continuous emotional problems pose additional challenges for the youngsters, especially if the availability of support at schools and at healthcare systems is restricted [ 5 , 7 ]. Several pre-pandemic studies also revealed that older adolescents report more mental health problems [ 11 ] and less physical activity [ 19 , 22 ], although studies examining adolescents’ well-being during pandemics did not find age differences [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, university students in China have been required to stay at home, in isolation, for longer periods of time, which may increase their risk of depression ( 3 ). Previous studies have shown that the COVID-19 pandemic has exerted negative psychological effects on people ( 4 6 ). Several cross-sectional studies have shown that Chinese university students experienced varying degrees of mental health problems during COVID-19 ( 7 9 ).…”
Section: Introductionmentioning
confidence: 99%